The Enactment of Knowledge Sharing: The Roles of Psychological Availability and Team Psychological Safety Climate - Qian, Jing; Zhang, Wei; Qu, Yi; Wang, Bin; Chen, Meng (Frontiers in Psychology, 2020)
Scholars have made great efforts to investigate the antecedents of knowledge sharing. In the current study, we applied the proactive motivation model (Parker, Bindl, and Strauss, 2010) to propose a theoretical model to advance this research line and examined the relationship between coaching and knowledge sharing. A total of 197 supervisor–subordinate dyads from a logistics company completed the survey questionnaire. Our results show that leaders’ coaching behavior positively relates to employees’ knowledge sharing behavior via psychological availability. Furthermore, our results show that team psychological safety climate moderates the relationship between psychological availability and employees’ knowledge sharing behavior, as well as the indirect effect between leaders’ coaching behavior and employees’ knowledge sharing.